Masdevallia hortensis - Vieira Uribe, Sebastian (2017)
Masdevallia hortensis is similar to most other species of Masdevallia subgenus Meleagris, it can be distinguished by the callus at the apex of the dorsal sepal and the revolute, white, lateral sepals with a red-purple mid vein. For a long time known only from the type locality where it became extinct by over-collecting, it has been recently rediscovered in two other nearby localities in the Cordillera Occidental in Antioquia and Risaralda, Colombia, where it grows as an epiphyte in shaded and very humid areas of the montane forests around 2600 m elevation.